Farming systems approach for ensuring food and nutrition security An ICAR-IIFSR initiative under Farmer First Programme - Prusty, A K; Kashyap, Poonam; Panwar, A S; Singh, M P; Shamim, M; Verma, Nisha; Jat, P C; Kumar, Sunil; Kumar, Sumit (Indian Farming, 2021)
Farmer First Programme, a flagship programme of Indian Council of Agricultural Research(ICAR) funded under ICAR KVK scheme is being implemented by ICAR-Indian Institute ofFarming Systems Research (IIFSR), Modipuram in 3 selected villages of Muzaffarnagar districtin western Uttar Pradesh. The prime objective of the project is to understand the constraints andopportunity available in the region along with designing and implementation of holistic farmingsystems interventions for ensuring food and nutritional security through increasing the farmproductivity and profitability with small and marginal farmers in focus. Under this programme,1,036 households in a cluster belonging to 3 contiguous villages i.e. Bhaingi-Bhangela, Satheriand Sonta in Khatauli block of Muzaffarnagar district were chosen for technological interventionin different modules of the farming system. Farming systems intervention proved to be a useful toolfor leveraging the small and marginal farmers for their livelihood security.